The Asian-African Conference1955 and Thai-Sino Relation Development - Piyasirikul, Kampol (Journal of Sinology (วารสารจีนวิทยา), 2009)
This article mainly discusses about the importance of the Asian-African Conference held in Bandung Indonesia in 1955 focusing on Thai-Sino relation development. This Conference actually provided Thailand and China a good occasion to discuss directly and understand each other. Certainly, this has bettered Thai-Sino relation. However, due to the change of political power in Thailand, the con-China policy was carried out again. Thai-Sino relation that seemed getting better had to be ceased temporarily. On the basis of the related research papers, the writer has attempted to make this article get ahead of and different from others. Thus, not only has the writer used Chinese historical primary sources, but also has employed some related historical archives seldom quoted by others from the archive library of the Ministry of Foreign Affairs of Thailand. According to the content of those archives, the writer has raised some new viewpoints to make the research as close as possible to perfection.